How Malleable Are Pro-environmental Preferences? Evidence from a Randomized Survey Experiment - Giorgia Menta; Michela Piccari; Bertrand Verheyden (Institute of Labor Economics (IZA), 2024)
With growing emphasis on sustainable practices, carbon taxes and congestion charges are emerging as key tools to reduce greenhouse gas emissions and improve air quality, yet they often face public resistance. Using longitudinal data from a randomized survey experiment in Luxembourg, this paper investigates whether providing relevant information about these two green mobility policies influences pro-environmental attitudes (stated support and willingness to pay for the carbon tax) and behaviors (carbon offsetting donations). The first treatment, which informs participants that public support for urban congestion charges tends to increase after implementation, has little to no effect. In contrast, information on the use of carbon tax revenues (redistribution and energy-efficient investments) has a large positive impact on both stated and revealed pro-environmental preferences. Our results indicate that support for the carbon tax is more elastic to information on its redistributive aspect, rather than on its use for funding green projects. Additionally, constraints to behavioral change and pre-treatment environmental attitudes play a role in treatment response heterogeneity, and show that confirmation bias can moderate responses to information, especially among those skeptical of climate science.
Keywords: D83; H23; H31; Q58; 330; survey experiment; climate policy; carbon tax; preferences; taxation; Luxembourg